Insights into oral bioavailability enhancement of therapeutic herbal constituents by cytochrome P450 3A inhibition. (2nd October 2021) - Chen, Junmei; Liu, Jinman; Huang, Yueyue; Li, Ruoyu; Ma, Cuiru; Zhang, Beiping; Wu, Fanchang; Yu, Wenqian; Zuo, Xue; Liang, Yong; Wang, Qi
Abstract: Herbal plants typically have complex compositions and diverse mechanisms. Among them, bioactive constituents with relatively high exposure in vivo are likely to exhibit therapeutic efficacy. On the other hand, their bioavailability may be influenced by the synergistic effects of different bioactive components. Cytochrome P450 3A (CYP3A) is one of the most abundant CYP enzymes, responsible for the metabolism of 50% of approved drugs. In recent years, many therapeutic herbal constituents have been identified as CYP3A substrates. It is more evident that CYP3A inhibition derived from the herbal formula plays a critical role in improving the oral bioavailability of therapeutic constituents. CYP3A inhibition may be the mechanism of the synergism of herbal formula. In this review, we explored the multiplicity of CYP3A, summarized herbal monomers with CYP3A inhibitory effects, and evaluated herb-mediated CYP3A inhibition, thereby providing new insights into the mechanisms of CYP3A inhibition-mediated oral herb bioavailability.